Battle of the bulge - Annakin, Ken.; Fonda, Henry, 1905-1982.; Shaw, Robert, 1927-1978.; Ryan, Robert, 1896-1958.; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2005)
Nazi Panzer forces stage a last-ditch Belgian front offensive that could turn the tide of WWII. A spectacular recreation of a crucial campaign.
Title from container.
Originally released as a motion picture in 1965.
Special features: new digital transfer from restored picture and audio elements; 2 vintage featurettes: The Filming of Battle of the Bulge; History Recreated; theatrical trailer.
Henry Fonda, Robert Shaw, Robert Ryan, Dana Andrews, Pier Angeli, Barbara Werle.
MPAA rating: Not rated.
DVD, region 1, widescreen presentation; Dolby surround 5.1.
Keywords: World War, 1939-1945 -- Drama; Feature films; Films for the hearing impaired